Peran Fermentasi Buah Morinda Citrifolia Sebagai Antimikroba - Elli Arsita; Calvin Sasongko; Erma Mexcorry Sumbayak (Jurnal Ners, 2026)
The development of germ resistance cases due to excessive use of antibiotics is rampant and alternatives that are used in replacing the role of antibiotics also vary, one of which is by utilizing plant components or better known as phytotherapy. Morinda citrifolia is an alternative example that can be used as phytotherapy. Morinda citrifolia used are ones that have been fermented for 14 days. Active compounds in Morinda citrifolia have many functions, one of which can be used as an antimicrobial. The aim of this study is to test the efficacy of Morinda citrifolia fruit fermentation as an antimicrobe. The method used in this study is to use a multilevel dilution system of Morinda citrifolia’s fermented liquid which is then followed by the method of discs and broth dilution. On the disc method, 50µl of each tube dilution will be taken, then dropped into the well in culture of Staphylococcus aureus and Escherichia coli. The broth dilution method is done to determine the inhibition and killing zone the minimum in both microbes. The effectivity of Morinda citrifolia fermentation on Staphylococcus aureus and Escherichia coli was proven by 100% concentration on Mueller Hinton media in order to form a inhibition zone of 13.95mm and 11.60mm. Inhibitory zone of 11.04 mm was formed in Staphylococcus aureus only at a concentration of 50%. Meanwhile, In the broth dilution method, Morinda citrifolia fermentation in both microbes has the same minimum killing rate at a concentration of 25%. Conclusion, Morinda citrifolia fruit fermentation is effective as an antimicroba.